The advantage of inhomogeneity: lessons from a noise driven linearized dynamical system - Máté, Gabriell; Néda, Zoltán (Physica. A, Statistical mechanics and its applications, 2016)
Dynamical systems composed of interacting elements are considered in the vicinity of a stable equilibrium state. In order to study the statistical properties of the fluctuations induced by an external noise-like perturbation an analytically tractable linearized model is introduced. Dynamical systems composed by elements with an idealized homogeneous and inhomogeneous coupling structure are investigated and compared. Our results prove and mathematically quantify the inertial, damping effects of the inhomogeneous construction. We motivate the study and the model from the perspective of economic and social systems. The expansion process of the European Union is taken as a specific example.